Validation of the Italian version of the Tool to Measure Parenting Self‐Efficacy questionnaire using data from an intervention study. (16th July 2022) - Roncaglia, Francesca; Bonvicini, Laura; Kendall, Sally; Panza, Costantino; Ferraroni, Monica; Giorgi Rossi, Paolo
Abstract: Background: Parent self‐efficacy (PSE), parents' confidence in their ability to successfully raise their children, has proved to be a powerful direct predictor of specific positive parenting practices. The aim of this study was to validate the Italian version of the Tool to Measure Parenting Self‐Efficacy (TOPSE) using data from the questionnaires previously completed in a controlled before–after study conducted in 2015 to evaluate a newsletter programme to help improve parenting. Mothers and fathers of newborns were asked to complete the TOPSE at the child's birth (t0), at 6 months (t1) and at 12 months (t2): 265 TOPSE questionnaires were collected at t0 (43%), 158 at t1 (26%) and 188 at t2 (31%). Methods: We measured internal reliability using Cronbach's alpha for each of the eight domains of the TOPSE. The intracluster correlation coefficient (ICC) was used to evaluate the external reliability only for parents with more than one child. Responsiveness was measured by testing the ability of the questionnaire to detect differences between groups and times that we expected to be measurable, based on consolidated findings in the literature. Mean scores of PSE improved from t0 to t2 (Hypothesis 1), PSE was lower at baseline for first‐time parents than for those with multiple children (Hypothesis 2) and the improvement from t0 to t2 was stronger for first‐time parents than for parents with multiple children (Hypothesis 3). Results and Conclusion: Based on our sample of questionnaires, the Italian version of the TOPSE was reliable for almost all of the domains except for Emotion, Self‐acceptance and Learning, which could be refined by re‐framing or dropping one item. External reliability was moderate, bearing in mind that the questionnaire was repeated at different times over 12 months, during which parents normally change. Responsiveness was good, especially for the Emotion and Empathy domains.